2014
DOI: 10.1007/s00234-014-1461-9
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of cerebrospinal fluid outflow: a deeper understanding of resorption

Abstract: Knowledge of the CSF pathways holds implications for our ability to understand, prognose, and even treat diseases related to CSF circulation and so is a matter of considerable relevance to neuroradiology and neurology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 62 publications
4
44
0
4
Order By: Relevance
“…Overall, these data demonstrated the delivery of a therapeutic enzyme from the CSF to the systemic organs after ICVadministration. Although the mechanism of enzyme delivery from the CSF to the systemic circulation is unclear, it has been suggested that the CSF containing IDS might communicate with the systemic venous circulation via the subarachnoid space (Chen et al 2015;Glimcher et al 2008;Higuchi et al 2012;Hladky and Barrand 2014). Nevertheless, these data should be further validated in the clinical setting, because CSF turn-over time via normal venous drainage is significantly different for mice and humans.…”
Section: (B)mentioning
confidence: 99%
“…Overall, these data demonstrated the delivery of a therapeutic enzyme from the CSF to the systemic organs after ICVadministration. Although the mechanism of enzyme delivery from the CSF to the systemic circulation is unclear, it has been suggested that the CSF containing IDS might communicate with the systemic venous circulation via the subarachnoid space (Chen et al 2015;Glimcher et al 2008;Higuchi et al 2012;Hladky and Barrand 2014). Nevertheless, these data should be further validated in the clinical setting, because CSF turn-over time via normal venous drainage is significantly different for mice and humans.…”
Section: (B)mentioning
confidence: 99%
“…1B). CSF is eventually cleared to the venous system through arachnoid villi, to the cervical lymphatics through the cribriform plate (11), and to the recently discovered meningeal lymphatics that line the dural sinuses (12). The trans-astrocytic water movements associated with CSF flow into and CSF/ISF flow out of the brain parenchyma are facilitated by aquaporin-4 (AQP4) water channels, which are localized along perivascular astrocytic end-feet that contribute to the blood brain barrier (1).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the current interest in CSF dynamics, non-invasive in-vivo methods for measuring glymphatic function are limited and the majority of existing data has been collected using animal models (5,13,16). 11 C-PiB is a neutral lipophilic benzothiazole PET tracer and is used to image A plaques in Alzheimer's disease (17) and, more recently, to quantify in vivo myelin loss and regeneration in multiple sclerosis (18). 11 C-PiB PET has also recently been used to quantify CSF clearance in humans (19).…”
Section: Introductionmentioning
confidence: 99%
“…It has been known for some years that lymphatic vessels exist in the meninges at the termination of the optic nerve subarachnoid space . Approximately 50% of cerebrospinal fluid (CSF) outflow occurs via lymphatics in rodents, with an unknown, probably smaller proportion occurring in primates and humans . Most of the lymphatic drainage originates along the olfactory nerves, but some occurs around the optic nerve termination …”
mentioning
confidence: 99%
“…5 Most of the lymphatic drainage originates along the olfactory nerves, but some occurs around the optic nerve termination. 6 A very novel model proposed is that CSF flows along the perivascular space surrounding the central retinal artery into the anterior optic nerve and retina and that interstitial fluid flows back out along the perivenular spaces back into the subarachnoid space surrounding the optic nerve. This could provide a route for the clearance of toxic metabolites like beta amyloid protein.…”
mentioning
confidence: 99%